FOMO Pada E-Commerce: Pengaruh Limited Quantity, Limited Time, Discount, Free Shipping Terhadap Arousal Dan Impulse Buying - Widyariini, Lydia Ari; Lilihata, Cysilya Frensea; Agrippina, Yulika Rosita (Institut Shanti Bhuana, Program Studi Kewirausahaan, 2025)
Abstract The FOMO strategy is implemented by retailers to influence consumers to feel concerned about missing out on the products they wish to purchase through a flash sale program. Information from the marketplace showing limited quantity, limited time for purchase, as well as price discounts and free shipping is expected to stimulate consumers' excitement (arousal) to make a purchase. This study aims to analyze the effects of limited quantity, limited time, price discount, and free shipping on perceived arousal and impulse buying on Shopee through the Flash Sale program. A quantitative analysis method using a survey was conducted by distributing an online questionnaire to 133 Shopee customers. The data were analyzed using Structural Equation Model (SEM), processed with Smart PLS (Partial Least Square) software. The results of the study show that limited quantity, limited time, price discount, and free shipping have an effect on perceived arousal and impulse buying. Perceived arousal also affects impulse buying. Kata kunci: Limited Quantity, Limited Time, Price Discount, Free Shipping, Perceived Arousal, Impulse Buying.